Предмет: Математика,
автор: christinakrasyuk
Срочно, с действиями!!
Спростить выражение и вичислить его значение при х=-5; -2(2,7х-1)-(6-3,4х)+8(0,4х-2).
Ответы
Автор ответа:
0
Ответ:
-26
Пошаговое объяснение:
-2(2,7х-1)-(6-3,4х)+8(0,4х-2)
-5,4х +2 -6 +3,4х +3,2х -16 = 1,2х - 20
При х = -5
1,2*(-5) -20 = -6-20=-26
Автор ответа:
0
-2(2,7х-1)-(6-3,4х)+8(0,4х-2)=-2(2,7*5-1)-(6-3,4*5)+8(0,4*5-2)=-2*12,5-(6-17)+0=-25+23=2
Похожие вопросы
Предмет: География,
автор: Lirinda
Предмет: Химия,
автор: svetoforn
Предмет: Алгебра,
автор: CheloVek0708
Предмет: История,
автор: ivahnenkoa9
Предмет: Математика,
автор: keyd1